Investigation of Dried Herbal Tea Production from Gymnema Sylvestre Leaf - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2018)
Diabetes mellitus is a major public health problem in the developed and developing countries. The Gymnema sylvestre is one of the important anti-diabetic medicinal plant. Gymnema sylvestre is a slow growing, perennial medicinal woody climber found in North of Vietnam. Gymnema sylvestre is useful in controlling blood sugar to treat type-II diabetes. Gymnemic acid, the active ingredient of this plant, is extracted from leaves. There is a growing demand for G. sylvestre leaves in the pharmaceutical trade. There was not any research mentioned to the production of herbal tea from Gymnema sylvestre. Therefore, objective of this study focused on the effect of blanching temperature and time; heat pump drying temperature and storage condition to Gymnemic acid (%), color (sensory score) of the dried Gymnema sylvestre tea. Results showed that Gymnema sylvestre should be blanched in hot water 95oC at 4 seconds in ascorbic acid 0.5% and then beeing dried by heat pump dryer at 40oC until 6.5% moisture. The final herbal tea could be preserved under vacuum in PET/AL/PE bag at 4oC to maintain antioxidant activity for 12 months. Gymnema sylvestre is most important for plant prospecting.Keywords: Gymnema sylvestre, Herbal tea, Blanching, Drying, Vacuum, Gymnemic acid.